Pengaruh Literasi Keuangan dan Experienced Regret Terhadap Keputusan Investasi Pada PNS Dinas Pemberdayaan Perempuan dan Perlindungan Anak, PPKB Provinsi Sumatera Barat - Gusriyanti Gusriyanti; Febryandhie Ananda (Akuntansi, 2023)
Investment decision is a problem faced by someone to allocate their funds in the form of investment as it will generate profits in the future. The purpose of this study is to determine the effect of financial literacy and experienced regret on investment decisions in PNS Women's Empowerment and Child Protection, PPKB West Sumatra Province. The sample in this study were 50 PNS Respondents from the Women's Empowerment and Child Protection Office, PPKB West Sumatera Province with a sampling technique that was purposive sampling. The analytical method used is multiple linear regression method. Based on the hypothesis, the results of the study show that the f-test that financial literacy and experienced regret used have an effect on investment decisions.